2021
DOI: 10.1021/acscatal.0c04894
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Acidity in Formation and Performance of Active Ni Single Sites in Supported Catalysts for Butene Dimerization: A View inside by Operando EPR and In Situ FTIR Spectroscopy

Abstract: A series of supported Ni/SiO2–Al2O3 catalysts with the same Ni content but different ratios of Brønsted and Lewis acid sites resulting from different Al/Si ratios have been prepared by impregnation with Ni­(Cp)2 and analyzed by operando electron paramagnetic resonance (EPR) during dimerization of n-butenes under industrially relevant conditions as well as by in situ Fourier transform infrared (FTIR) spectroscopy of adsorbed pyridine and CO to derive relations between the surface acidic properties, the nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…According to previous research studies, metallic state Pt (0) revealed the highest ORR activity. , Moreover, the binding energy of Pt/(Mn–N)@C at the Pt 4f doublet revealed a negative shift (0.13 eV) compared to Pt/XC-72R due to the electron donation from the (Mn–N)@C substrate to Pt. Compared to Pt/N@C, it also revealed a slight negative shift, indicating that the obtained electronic structure has been changed through the process of loading Pt on (Mn–N)@C. The downward shift of the d-band center resulted in the decrease of the electron return of the Pt 5d orbital, thus boosting the ORR. , …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to previous research studies, metallic state Pt (0) revealed the highest ORR activity. , Moreover, the binding energy of Pt/(Mn–N)@C at the Pt 4f doublet revealed a negative shift (0.13 eV) compared to Pt/XC-72R due to the electron donation from the (Mn–N)@C substrate to Pt. Compared to Pt/N@C, it also revealed a slight negative shift, indicating that the obtained electronic structure has been changed through the process of loading Pt on (Mn–N)@C. The downward shift of the d-band center resulted in the decrease of the electron return of the Pt 5d orbital, thus boosting the ORR. , …”
Section: Resultsmentioning
confidence: 98%
“…Compared to Pt/N@C, it also revealed a slight negative shift, indicating that the obtained electronic structure has been changed through the process of loading Pt on (Mn−N)@C. The downward shift of the d-band center resulted in the decrease of the electron return of the Pt 5d orbital, thus boosting the ORR. 51,52 The electrocatalytic performance of different Pt/carbon catalysts and carbon substrates toward ORR was evaluated in 0.1 M HClO 4 using the RDE method. Figure 3a shows the different CV curves of four catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…whose pyrrolic N 4 -metal coordination could exist without any vacancy. 27 , 28 Generally, the N 4 -Ni coordination requires relatively lower energy for ECO 2 RR than N 3 -Ni regardless of pyridinic or pyrrolic N coordination ( Figures 6 K and S24 ). This explains that why protein-based catalyst (N 4 -Ni coordination) presents better ECO 2 RR performance than EPS-based catalyst (mixture of N 4 -Ni and N 3 -Ni coordination).…”
Section: Resultsmentioning
confidence: 94%
“…Compared with Mn/Y, the weak acid sites of Mn/DY decreased but the proportion of strong acid increased. It is because some of the aluminum species (Si–O–Al–O–Si) in the Y zeolite framework were leached after dealumination, and these aluminum species often constituted the weak Brønsted acid sites of the zeolite . At the same time, the change in the position of Al species may increase the distance between adjacent Al, which can also lead to the enhancement of acidic sites.…”
Section: Results and Discussionmentioning
confidence: 99%